Development of Cookies Made from Breadfruit (Artocarpus altilis) and Plantain (Musa paradisiaca L.) with Different Levels of Ripeness - Sayuti, Kesuma; Refdi, Cesar Welya; Wellyalina, Wellyalina; Sari, Intan Derlia (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Indonesians still depend heavily on wheat flour for cookies, while the use of local foods such as breadfruit and plantain is not yet optimal. Breadfruit is a source of carbohydrates that is high in fiber and low in glycemic index. On the other hand, plantains at a certain level of ripeness contain natural sugars that can act as sweeteners while also affecting the glycemic index. Therefore, the combination of these two ingredients has the potential to produce healthier functional cookies that are suitable for diabetics. This study aims to evaluate the effect of using breadfruit flour and plantain flour with different levels of ripeness on the physicochemical characteristics and glycemic index of cookies. The study used a Completely Randomized Design (CRD) with 4 treatments based on the ripeness level of the plantain (green, greenish yellow, yellow, and yellow with black spots) and 3 replicates. The parameters observed included physical and chemical analysis. Based on the results of the study, it was found that the ripeness level of plantain in cookie formulations significantly affected the moisture content, fat content, protein content, carbohydrate content, dietary fiber content, starch content, total sugar content, glycemic index test, hardness test, colour test, and organoleptic test (colour, aroma, texture, and taste). But does not significantly affect the ash content in the cookie products. The best treatment was obtained in treatment D, which was bananas with a yellow ripeness level and black spots. Thus, it can be concluded that the ripeness level of plantain has a significant effect on the quality of the cookies produced, except for the ash content of the cookies. Cookies made with plantain with the highest ripeness level have the best balance of colour, taste, aroma, and texture, making them the most preferred by the panelists. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-BeingSDG 12: Responsible Consumption and Production